DESAIN POWER PULSE MAGNETIZER DENGAN VARIASI KAPASITANSI SEBAGAI PERANGKAT PEMBANGKIT MEDAN MAGNET PADA MATERIAL MAGNET FERRITE - Ade Fikri Fauzi (2023)
Pulse magnetic field engineering is necessary to study the physics of condensed bodies under high strength magnetic fields. The magnetic field engineering device that is created is usually called a magnetizer. A magnetizer is a tool used to magnetize magnetic or ferromagnetic objects that previously had no magnetic force. Research shows that increasing the capacitance results in a higher magnetic field without changing the parameters of the coil. Increase capasitance causes the maximum current pulse to change, affecting the intensity of the formed magnetic field. The author's design simulation process shows that an increase in capacitance values (11.2 mF), (33.6 mF), and (56 mF) results in a difference in the current pulse. Different current pulses have a different impact on the intensity of the magnetic field in each experiment. The results obtained are (2.6 T), (5.1 T), and (7 T), where the increase in magnetic field induction is directly proportional to the capacitance value. This is by research in reference journals, the data obtained shows that the application of the circuit can fulfill its role only with a capacitance of 11.2 mF. Because of the ferrite magnetic material, a maximum magnetic field intensity of 0.46 Tesla is obtained from the Y40 model. Meanwhile, the intensity of the magnetic field from the pulse generated by the 11.2 mF capacitor is 2.6 Tesla. So the application of pulsed current to magnetize Ferrite (Fe2O3) permanent magnetic material remains effective with the most negligible capacitance as long as the object diameter is <130 mm. This system can also magnetize Neodymium (NdFeB) magnetic materials with certain sample cut limits, due to the Neodymium permanent magnet (NdFeB) intensity of 1.45 Tesla on the N54 magnet.